Pengaruh Motivasi Kerja Dan Lingkungan Kerja Terhadap Kinerja Guru Di MTS Pangkalan Kerinci Kabupaten Pelalawan - Taufiqurrahman '; Sri Indarti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research is to find out the influence of work motivation variable and work place variable into teachers performance in MTS Pangkalan Kerinci Kabupaten Pelalawan simultaneously and partially. Sample is the smallest part of the population (Umar, 2003:138). To decide the sample, writer conduct a cencus to 63 teachers. data is analyzed descriptively, and quantitatively, using multiple linear regression. writer used SPSS for help. From simultant regression test ( F-test), we can see that work motivation and work place have significant impact to teachers performance. Partial test (t test) shows that work motivation has significant impact partially to teachers performance. while work place partially influence teachers performance.Keywords: work motivation, work place and teachers performance